Exploring Culinary Traditions of South Asia in Children’s Literature - Marothia, Ritika (THE PRIMARY TEACHER, 2025)
The article delves into children’s literature, particularly focusing on books that highlight culinary traditions from South Asia. These narratives not only introduce young readers to diverse cuisines and the significance of food, but also weave in themes of family, community, heritage, and growth. The central discourse emphasises character development within these stories and its impact on young readers. Through the lens of various books, the article elucidates how these characters reflect growth, teach empathy, establish values, and serve as role models